Representação de interesses no setor agrícola pós-desregulamentação: o Clube dos Amigos da Terra de Uberlândia - Barbosa, Gabriel José (2006)
The present research examines the Clube dos Amigos da Terra de Uberlândia ( Friends of the Earth Club of Uberlândia ), a specialized rural organization, in the context of the transformations in the representation of interests concerning the agricultural sector with emphasis on change in the institutional atmosphere of agribusiness. The research evaluates the importance of collective action with the objective of procuring benefits for the next generation of producers. A theoretical survey was elaborated and complemented by field research. Twenty seven interviews were conducted among agricultural producers and representatives of firms working in the area, using a semi structured instrument for the collection of qualitative data. Those interviewed were, also, members of the Club. Data were collected during the month of January, 2006. The questionnaires were interpreted and the data tabulated. The results revealed that the Club follows the standard of modern association. The members acted in defense of their economic interests as they established relations to strengthen the private sector with increased space for autonomous action as opposed to the regulatory function of the State.